Evidence From Artificial Intelligence in General Administrative Procedure - Dubiński, Łukasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
Artificial intelligence is becoming an element of everyday life, and also a part of administrative proceedings. The legislator systematically adds regulations that allow public administration bodies to use artificial intelligence. At the same time, the Code of Administrative Procedure has not been amended in this respect. The article tries to establish what artificial intelligence evidence is. In addition, the issue of whether the rules on administrative evidence should be changed to cover the use of AI evidence is examined.